OBJECTIVE CRITERIA OF PATIENT’S READINESS TO FREE AUTOPLASTY IN CASE OF GRANULATING WOUNDS (CRITERIA OF READINESS OF GRANULATING WOUNDS TO OPERATION) - Yu. V. Yurova; I. V. Shlyk; P. K. Krylov (Вестник хирургии имени И.И. Грекова)
The article based on the analysis of 84 follow-up of the patients. The authors suggested using the indices of microbiological and immunological investigations and data of laser Doppler ultrasonography to determine the readiness of granulating wound to free autoplasty. The data obtained allowed developing an algorithm of treatment, patient’s preparation to surgery and determination of operation terms.